DEVELOPMENT AND PRODUCTIVITY OF SESAME AS A FUNCTION OF PHOSPHATE FERTILIZATION AND USE OF CONDITIONING BACTERIA - dos Santos Lopes, Nailson; Theo Gentil, Kevin; Biotech Brasil, Green (Journal of Interdisciplinary Debates, 2021)
The sesame (Sesamum indicum L) is a crop of great importance due to its great economic potential and its use in several sectors such as gastronomy, cosmetics, medicines, biofuels, among others. With this, it is necessary to search for alternatives that allow the increase in its production without an increase in the exploitation of nonrenewable resources as in the case of phosphorus. The objective of this study was to evaluate the development and productivity of sesame seeds submitted to different doses of phosphorus, keeping nitrogen and potassium fertilization constant, as well as evaluating the effect of seed inoculation with Pseudomonas bacteria. The experiment was conducted at the Madeira Cortada Site, located in the rural area of Missão Velha-CE. The soil of the experimental area is classified as typical Red Yellow Latosol. The experiment was carried out in a randomized complete block design in a subdivided plot, with three replications. The plots were composed of four doses of phosphorus (0, 25, 50 and 100% of the recommended dose) and the subplots to the use of PhosfoBarvar inoculant (with and without), totaling 24 observations. Each plot measures three meters wide by three meters in length, totaling 9 m2. The data were analyzed by analysis of variance (ANOVA) and by the F test and submitted to the polynomial regression test, determining the response curve of each variable. The program used to analyze the data was SISVAR. The following variables were evaluated: plant height, stem diameter, pod length, pod / plant number, grain / plant number, 1000 grain mass, pod yield, grain yield and yield. The fertilization interaction and PhosfoBarvar did not present differences for the variables. Fertilization showed a significant difference at 5% for stem diameter and pod length and significant at 1% for the number of pod / plant, pod productivity and grain yield. Phosfobarvar showed no significant difference for the variables number of grains per pod, mass of 1000 grains, and yield. In the other variables, it presented a significant difference at 5%. Therefore, it was observed that the phosphate fertilization and the use of the bacteria brought benefits for the sesame production, and the bacterium was responsible for an increase of 278 kg ha-1 and 143 kg ha-1 in grain yield and grain yield, respectively. necessary to carry out other work in order to prove the benefits of the treatments applied.